Effects of Marriage Preparation Per Satir's Communication Model and Narrative Therapy on Empathy and Emotional Expression in Single Young Adults - Amir Abbass Boostani Kashani; Anahita Khodabakhshi-Koolaee; Hussein Davoodi; Hassan Heidari (Iran University of Medical Sciences, 2020)
Background: Empathy and emotional expression, as important psychological elements, significantly impact couples' marital satisfaction. Premarital counseling models are designed to increase positive couples' communication behaviors and emotional style. Accordingly, this study compared the effects of marriage preparation based on Satir's communication model and narrative therapy on empathy and emotional expression in single young adults.  Methods: This quasi-experimental study employed a pre-test, post-test and a control group design. The research population included all girls and boys on the age of marriage who were referred to Vesta Counseling Clinic in Kashan City, Iran, from March 20th, to September 22nd, 2019. The study participants were 45 individuals who were selected by convenience sampling method. Then, they were randomly assigned to three groups (narrative therapy intervention, Satir intervention, and controls) of 15 clients. The research participants in the two intervention groups attended 11 sessions of narrative therapy and Satir communication therapy; however, the controls received no intervention. The data collection instruments were the Emotion Expression Scale (EES), and the Questionnaire Measure of Emotional Empathy (QMEE). The research hypotheses were tested using the Multivariate Analysis of Covariance (MANCOVA) by SPSS. Results: The present study results suggested that narrative therapy (F=53.97, P=0.0001) was more effective than Satir's communication model (F=33.82, P=0.0001) in terms of emotional expression. Both intervention groups obtained higher mean scores on emotional expression, compared to the controls (F=29.005, P=0.0001). Besides, the narrative therapy group gained a higher Post-test mean score for empathy (F=101.12, P=0.0001), compared to the Satir group (F=84.93, P=0.0001). Besides, both interventions were more effective in the test groups, compared to the controls (F=68.27, P=0.0001). Conclusion: Narrative therapy was more effective for improving emotional expression and empathy, compared to Satir's communication model. Family and marriage counselors are recommended to apply these premarital models for young single adults in counseling centers.